Activity of Noni Fruit (Morinda citrifolia L.) Ethanolic Extract on Class mu Glutation S-Transferase of Lung Rat - Purwanto, Purwanto; Martono, Sudibyo (Indonesian Society for Cancer Chemoprevention, 2020)
One of the main modalities of cancer treatment is chemotherapy, which uses chemicals that are generally electrophilic. These xenobiotic compounds sometimes does not produce effective response due to activity of glutathione S-transferase (GST) which inactivate the xenobiotics. Several natural phenolic compounds were reported to inhibit GST activity in vitro. Noni fruit (Morinda citrifolia L.) which contains flavonoids and other phenolic compounds such as scopoletin and morindon is proposed to interfere GST activity. This study aimed to analyze the effect of ethanolic extract of Noni fruit in vivo on GST activity in lung rat using 1,2-dichloro-4-nitrobenzene (DCNB). This substrate is a specific for class mu GST. First, rats were administered with ethanolic extract of Noni and dimethylbenz(α)anthracene (DMBA) for two weeks. The cytosolic fraction of lung was isolated then the GST activity was determined by simple kinetic program which was automatically calculated using spectrophotometer. The results showed that ethanolic extract of Noni in 1 and 5% (w/v) of concentration induced class mu GST activity, whereas 10% (w/v) of concentration inhibited class mu GST activity. After a treatment with DMBA, all tested concentrations of ethanolic extract of Noni inhibited class mu GST activity of lung rat significantly. These results indicated that Noni fruit extract can be further developed as a supportive agent of a chemotherapy drug.Keywords: DMBA, GST, Morinda citrifolia L., spectrophotometer.